Fluid-structural analysis of modular floating solar farms under wave motion - Sree, Dharma K. K. (2022)
Floating solar farms (FSFs) are emerging to be a viable option for large scale solar power production. The present study develops an original approach for the design assessment of the maximum stress/strain and displacement of massively connected modular FSFs under wave action. The scope includes two parts: (1) numerical simulations for the fluid structural analysis with two-way coupling of a global array of connected modular floaters that hold the massive number of solar panels; and (2) experimental validation of the numerical predictions for the dynamic response of the global array under wave action. The numerical approaches are based on finite element simulations. Both static and dynamic simulations are carried out with and without using the Fluid Structure Interaction (FSI) method, under different incident wave characteristics, rheological properties of the global array, and mooring configurations. The experiments were performed with a flexible perforated sheet using Froude scaling for dynamic similitude, with ultrasonic measurements to quantify the wave profile as well as the displacement responses of the array under wave action. The comparison shows reasonable agreement between the predictions and measurements at discrete locations along the array. Finally, a summary is provided on how the new approach can aid in the design assessment of modular FSFs under wave motion.